Harmoni dalam Keragaman: Potret Komunikasi Antarbudaya di Sekolah Dasar: Studi Kasus UPT SPF SD Negeri Labuang Baji I - Masalam, Fatmawati; Mahmud (Jurnal Dakwah Tabligh, 2025)
This research aims to examine the implementation of multicultural education at UPT SPF Labuang Baji I Elementary School from the perspective of intercultural communication. Multicultural education is seen as a strategic effort to instill values of tolerance, justice, appreciation for diversity, and to build intercultural competence from an early age. Using a qualitative case study approach, data was collected through interviews, observations, and documentation to gain an in-depth understanding of multicultural education practices in elementary schools. The results of the study show that the school has integrated the principles of inclusivity, justice, and dialogue into the curriculum and learning activities. The communication patterns among students from various cultural backgrounds are quite harmonious, although barriers such as stereotypes and differences in communication styles still exist. The role of teachers as mediators of intercultural communication is a crucial factor in creating a conducive learning environment.